Southernizing Arab criminology - Ouassini, Anwar (Southernising criminology, 2024)
In the dominance of Northern criminology, the experiences and knowledge of and from the Arab world have long lingered in the periphery. The Global North possesses a hegemony over the discipline with presupposed universal theories and laws that often ignore the contributions and diversity of the Global South. In a region of 22 nations and around 450 million citizens, traditional Northern academia has reduced Arab criminology to lawlessness, political violence, barbarism, instability, and religious totalitarianism. The project of Southernizing criminology presents an opportunity for cognitive justice that empowers and situates Arab criminology and other regions of the Global South in a position to participate in the democratization of criminological knowledge. This chapter will contend that Arab criminology is a necessary component of Southernizing criminology, requiring a dialogical relationship centered on confronting the prevalence of Orientalism and Islamophobia in Northern criminology.